Modelling of Surface Permeation in Multiple-Orifice Permeable Road - Yau Seng Mah, Darrien; Ling Loh, Siew; Abdul Mannan, Md; Hashim Wan Ibrahim, Wan (International Journal of Engineering and Technology, 2018)
A patent-pending StormPav green pavement is introduced here as a form of permeable road, in which the system employed precast concrete pieces as modular units. The pavement layer consists of hexagonal plates with each a service inlet to drain water. This study is exploring the water draining capability or technically surface permeation of these service inlets. Virtual and physical modelling are performed to investigate the service inlets as multiple orifices to permeate surface water of the said permeable road. Both modelling efforts have deduced that the permeable road has 18,000 â€“ 24,000 mm/hr of permeation rate when subjected to a 5-minute red-alert storm (>60mm/hr of intensity). It implies that StormPav green pavement has superior surface permeation against the forming of water ponding and flash flood on roads.Â